Volta phase plate cryo-EM of the small protein complex Prx3 - Maryam Khoshouei (Nature Portfolio, 2016)
Although the resolution achievable with cryo-EM can now rival crystallography, its application to small protein assemblies remains challenging. Here the authors demonstrate the use of the Volta phase plate for single particle analysis and its potential for the study of small specimens.